Pornografi Ditinjau dari Hukum Positif dan Hukum Pidana Islam - Siti Risdatul Ummah (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2017)
At the present time the development of social media so rapidly, which of course affect the pattern of community life. But this development is often misused, one of which is cyberpor. This paper aims to describe and analyze pornography in the perspective of Indonesian Penal Code and Islamic Criminal Law. At the end of the paper it is concluded that, first, pronography in Indonesian criminal law is defined as drawings, sketches, illustrations, photographs, writings, sounds, sounds, moving pictures, animations, cartoons, conversations, gestures, or other forms of communication through various forms of communication media and/or public performances, containing obscenity or sexual exploitation in violation of moral norms in society. The regulation is contained in the Criminal Code (Article 282), in Act Number 44 of 2008 on Pornography, and in Law Number 11 Year 2008 on Information and Electronic Transactions. Secondly, that pornography in Islamic Law includes adultery that is not punished (hadd), but still makes the perpetrators sinful. The sanction for the perpetrators of pornography is ta'zir, which the determination of sanctions is the right of the state leader in accordance with the level of crime committed.